Experimental determination of effective fast neutron removal cross-section and gamma attenuation coefficients in colemanite-modified fly ash geopolymers - Baykara, Oktay; Tanyildizi, Harun; Coskun, Ahmet (Pergamon-Elsevier Science Ltd, 2026)
The development of sustainable materials for hybrid neutron-gamma radiation shielding requires accurate characterization of attenuation behavior under realistic irradiation conditions. In this study, the neutron and gamma ray shielding performance of fly ash-based geopolymer mortars modified with colemanite (CM) was experimentally investigated. Neutron attenuation measurements were performed using a Pu-Be source in a modified howitzer system, and the results were evaluated in terms of effective fast neutron removal cross-section (Sigma(r),eff). Gamma ray attenuation properties were determined at photon energies between 356 and 1332 keV using a NaI(Tl) detector under a narrow beam geometry. The obtained Sigma(r),eff values ranged from 0.1531 to 0.1984 cm 1 , corresponding to approximately 47-54% neutron attenuation efficiency, depending on the colemanite content and sample thickness. Gamma-ray results showed that the mass attenuation coefficient (mu/rho) decreased as photon energy increased, but an improvement of up to 60% was observed with increasing CM content at low energies. Mechanical tests showed that the addition of 5% CM increased compressive strength, while higher contents led to a significant decrease due to microstructural degradation. The results demonstrate that colemanite addition effectively improves radiation shielding performance through combined neutron decelerationabsorption mechanisms and density-focused gamma attenuation. An optimum composition at 5% CM was determined, providing a balanced combination of mechanical integrity and shielding efficiency.
Keywords: Radiation Shielding; Neutron Attenuation; Gamma-Ray Absorption; Geopolymer Mortar; Colemanite; Mechanical Properties